2008
DOI: 10.1111/j.1745-4549.2007.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Baking Properties of Milk Protein-Coated Wheat Bran

Abstract: Increasing the dietary fiber content of formulated foods will benefit the health and nutrition of consumers. The problem is that it is difficult to add substantial amounts of dietary fiber to formulated foods. Fiber absorbs significant amounts of water from surrounding ingredients creating texture problems such as soggy and dry patches in the foods. In this study, red wheat bran milled and sieved smaller than 140 microns was coated by spraying with a 50/50 emulsion of whey protein isolates (WPIs) and casein. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…This may be due to the water‐holding capacity of the wheat bran and the particle size of the corresponding rehydrated particles. Onwulats () found that dietary fibre absorbed water from the environment. Also, de Moraes et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the water‐holding capacity of the wheat bran and the particle size of the corresponding rehydrated particles. Onwulats () found that dietary fibre absorbed water from the environment. Also, de Moraes et al .…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the water-holding capacity of the wheat bran and the particle size of the corresponding rehydrated particles. Onwulats (2008) found that dietary fibre absorbed water from the environment. Also, de Moraes et al (2013) reported that an increase in particle size leads to an increase in water-holding capacity values, indicating that the particle size can affect these parameters.…”
Section: Changes In Physicochemical During Storagementioning
confidence: 99%
“…However, small amounts of bran fibre up to 12% have been reported to have no negative impact on extrudate textural qualities (Huber, ). Some studies even reported that addition of a small quantity of fibre up to 8% improved crispiness of the expanded products by improving dough's water‐binding capacity and stability (Onwulata, ). Accordingly, fibres of high purity with small particle size did not cause any negative impact on textural qualities of extruded products in the present study, except at the highest level of protein addition.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of wheat bran addition on dough and bread properties have been extensively investigated. Bran fi bre absorbs signifi cant amounts of water from surrounding ingredients and creates textural problems, such as soggy and dry patches, in foods (ONWULATA, 2007).…”
mentioning
confidence: 99%